2012
DOI: 10.1159/000338202
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Toxic Epidermal Necrolysis with the Combination of Infliximab and High-Dose Intravenous Immunoglobulin

Abstract: Background: Therapeutic evidence for toxic epidermal necrolysis (TEN) is indicative for high-dose intravenous immunoglobulin yet inconclusive for corticosteroids. Objective: To describe the combination of corticosteroids, infliximab and a high-dose intravenous immunoglobulin course for TEN. Patients and Methods: In three patients (SCORTEN survival probabilities: 41.7%, 64.2%, 41.7%) disease control was evaluated by (a) employing quantitative image analysis to measure progression of skin detachment and (b) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
1
22
0
1
Order By: Relevance
“…Extensive epidermal keratinocyte cell death via cytotoxic T-cell stimulation, activation of Fas-Fas ligand interactions, and increased TNFa levels locally in the skin and in the circulation underlie the pathogenesis of TEN. It is suggested that the present combination modality efficiently arrests the detrimental progression of this condition through targeted modification of the above pathophysiologic aberrations [4]. Pharmacologic targeting of increased TNFa levels in TEN patients seems to be a promising emerging treatment strategy [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive epidermal keratinocyte cell death via cytotoxic T-cell stimulation, activation of Fas-Fas ligand interactions, and increased TNFa levels locally in the skin and in the circulation underlie the pathogenesis of TEN. It is suggested that the present combination modality efficiently arrests the detrimental progression of this condition through targeted modification of the above pathophysiologic aberrations [4]. Pharmacologic targeting of increased TNFa levels in TEN patients seems to be a promising emerging treatment strategy [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the present combination modality efficiently arrests the detrimental progression of this condition through targeted modification of the above pathophysiologic aberrations [4]. Pharmacologic targeting of increased TNFa levels in TEN patients seems to be a promising emerging treatment strategy [4]. However, designing trials to prove the efficacy of a therapeutic approach in a rare and serious disease as is TEN is not without any pitfalls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 There have been multiple studies examining the efficacy of IVIG in SJS/TEN patients, and the results have been inconsistent regarding survival rates and length of hospitalizations. 83,[104][105][106][107] Interestingly, the initiation of IVIG during the acute phase does not appear to diminish the severity of later ocular complications. 20 20 They determined that systemic modulation had no significant effect on final visual acuity or the incidence of chronic ocular complications.…”
Section: Ivigmentioning
confidence: 99%
“…There are many reports[169170171172173174] of successful use of Infliximab, and a few of etanercept (LOE5). It has been used alone, as well as in combination with IVIG and steroids, producing rapid response.…”
Section: Connective Issue Disordersmentioning
confidence: 99%